Mms22-Rtt107 axis attenuates the DNA damage checkpoint and the stability of the Rad9 checkpoint mediator - Bingbing Wan; Danying Guan; Shibai Li; Tzippora Chwat-Edelstein; Xiaolan Zhao (Nature Communications)
Abstract The DNA damage checkpoint is a highly conserved signaling pathway induced by genotoxin exposure or endogenous genome stress. It alters many cellular processes such as arresting the cell cycle progression and increasing DNA repair capacities. However, cells can downregulate the checkpoint after prolonged stress exposure to allow continued growth and alternative repair. Strategies that can dampen the DNA damage checkpoint are not well understood. Here, we report that budding yeast employs a pathway composed of the scaffold protein Rtt107, its binding partner Mms22, and an Mms22-associated ubiquitin ligase complex to downregulate the DNA damage checkpoint. Mechanistically, this pathway promotes the proteasomal degradation of a key checkpoint factor, Rad9. Furthermore, Rtt107 binding to Mms22 helps to enrich the ubiquitin ligase complex on chromatin for targeting the chromatin-bound form of Rad9. Finally, we provide evidence that the Rtt107-Mms22 axis operates in parallel with the Rtt107-Slx4 axis, which displaces Rad9 from chromatin. We thus propose that Rtt107 enables a bifurcated “anti-Rad9” strategy to optimally downregulate the DNA damage checkpoint.